The relationship of online learning to the quality of learning and the level of satisfaction of anesthesiology nursing students after the COVID-19 pandemic - Marselinus Widi Rahmanta; Ratih Kusuma Dewi; Astika Nur Rohmah (Universitas 'Aisyiyah Yogyakarta, 2023)
The COVID-19 pandemic has had an impact on the field of Education. Online learning is carried out to bring up various types of learning interactions in order to produce the quality of learning as expected. The level of student satisfaction shows how relevant the quality provided by the learning is. This study aims to determine the relationship between online learning and the level of satisfaction of Anesthesiology Nursing students after the COVID-19 pandemic at 'Aisyiyah University Yogyakarta. This study used a Cross Sectional quantitative approach with a correlation research design. The sampling technique used Total Sampling, totaling 142 respondents with restriction criteria. Data analysis using the Spearman Rank statistical test. The results showed that online learning for Anesthesiology Nursing students after the COVID-19 pandemic was included in the poor category by 4.2%, the good category by 50%, and the very good category by 45.8%. The quality of learning in students after the COVID-19 pandemic is included in the poor category of 18.3%, the good category of 58.5% and the very good category of 23.2%. The level of student satisfaction after the COVID-19 pandemic was dissatisfied with online learning by 6.3%, the satisfied category by 62% and the very satisfied category by 31.7%. The results of the Spearman Rank correlation test to determine the relationship between online learning and student learning quality obtained results of 0.000 (p < 0.05). The results of the Spearman Rank correlation test to determine the relationship between online learning and student satisfaction levels obtained results of 0.000 (p < 0.05). There is a significant relationship between online learning on the quality of learning and the level of satisfaction of Anesthesiology Nursing students after the COVID-19 pandemic at Universitas 'Aisyiyah Yogyakarta. Further research is needed using other variables related to online learning, learning quality and student satisfaction levels.